The Oneiric, the Spectral, and the Numinous: A Study of the Fantastic in Six Contemporary Central American Flash Fictions - Hernández-Gutiérrez, Antony (2026)
This article analyzes the fantastic in six contemporary Central American flash fictions selected from Aquí hay dragones. Breve antología de minificción centroamericana contemporánea (2016). The main objective is to examine how the fantastic is configured within the macro-categories of the oneiric, the spectral and the numinous, aiming to expand the academic discussion on fantastic flash fiction in the Central American region. Methodologically, the study adopts a hermeneutic and comparative approach, drawing from theories of the fantastic (Roas, 2001; Campra, 2001; Caamaño Morúa, 2014) and literary concepts such as the oneiric space (Luna Sellés, 2002), the aesthetics of delirium (Acevedo et al., 2020), and the unusual (Alemany, 2019). The analysis highlights that the selected texts share characteristics such as spatial dislocation and narrative fragmentation, which contribute to the construction of the fantastic. Additionally, it emphasizes how Central American flash fiction incorporates themes such as identity, migration and the disruption of reality. Finally, the study concludes that the fantastic remains relevant in Central American literature, with works that blend classical and contemporary elements, underscoring the need to further explore the genre and make its manifestations in the region more visible.